Beasts & behemoths : a young adventurer's guide - Zub, Jim; King, Stacy; Wheeler, Andrew (Graphic novelist) (Dungeons & dragons young adventurer's guide., 2020)
An illustrated guidebook to unusual creatures and monsters players can use to tell their own "Dungeons & Dragons" stories and RPG games. Discusses and explains each creature's abilities and magical powers, from the tiny swarming cranium rats to the massive, mystical, epic Tarrasque.